(untitled) (International relations and international law Journal, 2019)
Political and ideological policies of post-socialist countries to rehabilitate peoples make it necessary to study the problem of deportation and repression of «punished» peoples and groups belonging to the European groups of Kazakhstan’s nationality. The process of deportation of peoples that took place in the Soviet Union during one of the hard and difficult periods of its history in the years after the Second World War. Soviet society could be divided in relation to the functioning regime of power, and in this situation the authorities did everything so that its positions were not shaken, the measures applied to individual peoples and groups of the population, speaking in open or hidden form against the regime were tightened. With the beginning of the Second World War, the deportation took a new impetus of Soviet geopolitics. Poles and Germans were the largest national group of all those subjected to forced relocation. In special echelons, they were promptly exported to 107 settlements of Siberia and northern Kazakhstan. From the occupied territories of the Baltic states, the Poles and other undesirable elements of Soviet power were evicted. Finns and Karelians living in Kazakhstan from the 1930s were deported from the Leningrad Region in 1935–1940. The deportation policy was «explained» by a whole range of reasons. For example, deported from the Baltic countries, the western regions of Ukraine and Belarus, Moldova to Kazakhstan, were considered «unreliable», they were given preventive measures (linked by confessional factors, anti-reform measures, participation in gangs, belonging to the institutions of the outdated system). Key words: Geopolitical deportation, diaspora, World War II, European peoples, historical memory, historical destinies.